Development of semi-dehydrated mango for pie filling - Novilla, Mariannie Irabon (2006.)
This study on the development of semi-dehydrated mango for pie filling is primarily concerned with the lenghtening o shelf life of mango pie.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Mango; Pie filling